Establishment of emotional database and extraction of color psychology of children from images - Seunh-Yoon Shin (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In the modern society, there is a rapid increase in the need for color psychotherapy for psychological stability and environmental adaption of children for whom the interests of the parents are lacking in the midst of their busy daily schedules. Accordingly, we need to assess the emotional state of children through their drawings, etc. In this thesis, identification is made on color harmony by utilizing information of single and mixed colors in the color image space. Moreover, system for extraction of color psychology from the drawings of children is developed. First, emotional database is established on the basis of color image space. Then, enormous color values are group by clustering the images through the use of K-Means clustering. Emotions are extracted through matching with the database and child’s color psychology is examined by using color distribution chart. Empirical researches on sensibilities that are currently in progress are being pursued largely from psychological and engineering perspectives. Sensibility being understood in the area of psychology can be deemed close to being emotions. Meanwhile, sensibility understood from the engineering perspective can be defined as highly advanced psychological experiences induced in the minds of human beings from perception or cognition by external physical stimulation. This thesis demonstrated the overall excellence through experiment.